Penerapan Teknologi Augmented Reality Dengan Metode Marker Based Pada Aplikasi Pengenalan Jurusan Resiskom Berbasis Android - Erliana Dewi; Dwi Setyowati; Harmastuti - (Jurnal Teknologi, 2021)
Computer Systems Engineering is one of the majors at the Institute of Science & Technology AKPRIND Yogyakarta. Every year the department makes a brochure that is used to introduce the department, but only contains image and text information that is printed on a sheet of paper, so that readers cannot see the information digitally. To make brochures more attractive, they need to be enriched with Augmented Reality technology.Augmented Reality technology based on Android can be used as an approach to create applications, which are built using Unity 3D and Vuforia. In designing the application, the marker-based method is used, printed brochures are used as a medium for scanning markers so that applications can display information in the form of videos and 3-dimensional objects. Testing using black box and compatibility The results of the study resulted in an application for the introduction of the Android-based Computer System Engineering Department by applying Augmented Reality technology, which was named Resiskom AR Brochure. testing with the black box method is carried out on the Resiskom AR Brochure application, the application can run according to the expected goals and results. The compatibility test results show that the application can run well on various mobile platforms, different android versions, sizes, and screen resolutions.